Menumbuhkan Karakter Disiplin dan Tanggung Jawab Dalam Mengelola Keuangan Pribadi Siswa. - Amanda Salsabila Rahman; Rizka Diyah Suryani; Siti Maesaroh (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This Community Service Program was conducted to foster discipline and responsibility among students of SMK Media Informatika through personal financial management education. Low financial literacy among vocational school students is a critical issue, considering their readiness to enter the workforce and achieve financial independence. The program was implemented using educational methods, interactive discussions, case studies, and simple financial management simulations covering budgeting, financial recording, and priority setting. The results showed an improvement in students’ understanding of personal financial management concepts as well as positive changes in attitudes toward more disciplined and responsible financial decision-making. This program highlights the importance of financial education as a life-skill-based character development strategy to prepare vocational students for future financial challenges.